EXPRESSION OF CD44 AND CD24 MARKERS IN BIOPSY SAMPLES OF TRIPLE NEGATIVE BREAST CANCER PATIENTS BEFORE TREATMENT - S. G. Smirnova; N. V. Orlova; I. A. Smirnova; N. Yu. Dvinskikh; A. A. Charitonova; M. V. Kiseleva; I. A. Zamulaeva (Сибирский онкологический журнал)
The role of the expression of CD44 and CD24 in breast cancer (BC) has been explored in many laboratories around the world to identify predictive markers of tumor aggressiveness and patient’s response to anticancer therapy. These proteins participate in the process of tumor growth, metastasis and formation of cancer stem cells (CSCs). The study of CD44 and CD24 expression in triple negative (TN) BC, which is the most aggressive breast cancer subtype, is of particular interest. The aim of this study was to determine the relationship between the expression of CD44 and CD24 markers in biopsy samples of TNBC patients before treatment and clinical/ morphological characteristics of the tumors. Material and Methods. The study group included 67 patients with stage I–IV TNBC. Flow cytometry was used to determine the proportion of cells with CSC immunophenotype (CD44+/CD24-/low) in biopsy samples from the primary tumor of 65 patients and lymph nodes of 6 patients. In addition, the proportion of cells with all possible combinations of expression of these surface proteins was estimated. Results. Cells with CSC immunophenotype were detected in all patients with a wide individual variability of CSC proportion from 0.4 % to 77.0 % (median – 10.9 %). There were no differences in the proportion of CSCs in the primary tumor and lymph nodes. No statistically significant correlation between the proportion of CSCs in the primary tumor and the clinical/morphological parameters, including tumor size and differentiation grade, evidence of regional or distant metastases, tumor, size of the fraction of proliferating cells estimated by Ki67 expression, was found in either single or multivariate analysis. There was also no association of the above parameters (except Ki67) with immunophenotypes. A high proportion of Ki67-positive cells in the primary tumor was associated with the CD44-CD24-phenotype. Conclusion. The expression of CD44 and CD24 in biopsy samples of TNBC before treatment did not correlate with the clinical and morphological characteristics of the tumors, excepting Ki67 expression.